Disinformation Order and Social Media Algorithmic Trap: New Challenges for Sustainability of the Indonesia’s United Nation-State Narrative and Liberal Democratic Norms - Ahmad, Nyarwi (Jurnal Politik Indonesia: Indonesian Political Science Review, 2022)
The Internet and social media have been increasingly adopted by political entities across the globe. The consequences of such adaptations on the Indonesia’s nation-state narrative and liberal democratic norms have been under-researched however. This article argues that in democratic countries, such adaptations are likely to pave the way for the emergences of disinformation order and social media algorithmic trap. Within the specific context of Indonesia’s democracy, these disinformation order and social media algorithmic trap are likely to polarize political spheres and jeopardize not merely Indonesia’s united nation-state narrative, but also Indonesia’s liberal democratic norms that evolved since the post-reform era. To evaluate such propositions, this article adopts a desk study and selects Jakarta’s 2017 Gubernatorial Election as a study case. Learning from these desk study and study case, this article proposes the following arguments. To manage the consequences of disinformation order and social media algorithmic trap on politics and democracy, we need formulate new political communication and policy research agenda based on the following dictum: who get lost by what/whom in which channel/medium and with what effects. Taking such effort may give us an opportunity to keep the current Indonesia’s united nation-state narrative prevailing and liberal democratic norms flourishing.